The Venomics of Bothrops alternatus is a Pool of Acidic Proteins with Predominant Hemorrhagic and Coagulopathic Activities - Oehler, Michaela; Georgieva, Dessislava; Seifert, Jana; von Bergen, Martin; Arni, Raghuvir K. [UNESP]; Genov, Nicolay; Betzel, Christian (Amer Chemical Soc, 2010)
The venom proteome of Bothrops alternatus, a venomous snake widespread in South America, was analyzed by 2-D electrophoresis followed by mass spectrometric analysis and determination of enzymatic activities. The venomic composition revealed that metallo- and serine proteinases play primary roles in the pathogenesis of the envenomation by this pitviper. The identified 100 venom components with molecular masses from 10 to 100 kDa belong to six protein families: metalloproteinases, serine/thrombin-like proteinases, phospholipases A(2), L-amino acid oxidases, disintegrins and thrombin inhibitors. Metalloproteinases predominate and belong exclusively to the P-III class including the most potent hemorrhagic toxins. They represent 50% of all identified proteins. Two isoforms were identified: homologous to jararhagin, a hemorrhagic toxin, and to beritractivase, a nonhemorrhagic and pro-coagulant metalloproteinase. The B. alternatus venom is a rich source of proteins influencing the blood coagulation system with a potential for medical application. The isoelectric points of the components are distributed in the acidic pH range (the p/values are between 4 and 7) and no basic proteins were detected.
Keywords: Snake venomic; Bothrops alternatus; 2-D electrophoresis